Pertussis Vaccination for Adults: An Updated Guide for Clinicians - Kay Choong See (Vaccines)
Pertussis, or whooping cough, is a highly contagious respiratory infection caused by the Gram-negative bacterium Bordetella pertussis. Although traditionally associated with children, pertussis is increasingly prevalent among adults, particularly those with comorbidities or weakened immune systems, where it can lead to severe complications. Diagnosing pertussis in adults can be challenging due to its nonspecific symptoms, underreporting, and the limited sensitivity of available diagnostic tests. While treatment with macrolides is generally effective, it may not significantly alter the clinical course of the disease, and growing concerns about macrolide resistance are emerging. Vaccination remains the cornerstone of prevention, offering proven immunogenicity, efficacy, and safety. However, vaccination uptake remains low, partly due to limited patient awareness and insufficient prioritization by healthcare professionals. This review aims to provide clinicians with critical insights into pertussis epidemiology, vaccination strategies, and the latest guideline recommendations, empowering them to engage in meaningful discussions with adult patients and advocate for increased vaccination to combat this often-overlooked infection.